Optimalisasi Pemeriksaan Indeks Massa Tubuh dan Rasio Pinggang-Pinggul untuk Deteksi Dini Risiko Stroke pada Populasi Usia Produktif - Arwinder Singh; Alexander Halim Santoso; Farell Christian Gunaidi; Muhammad Adam Abizar Rafi; Muhammad Kevin Dava Pratama (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2025)
Stroke is a leading cause of death and long-term disability in Indonesia, with central obesity as one of the main risk factors. This community service activity was carried out in Grogol Village, West Jakarta, with anthropometric screening in the form of measuring Body Mass Index (BMI) and Waist-to-hip Ratio (WHR) in 67 productive age participants. The measurements were carried out by the Faculty of Medicine team at Tarumanagara University using calibrated standard measuring instruments. The screening results showed that 67.16% of participants were obese based on BMI and 73.13% had high WHR indicating central obesity. Education on healthy eating patterns, increased physical activity, and recommendations for further medical examinations were provided as an effort to prevent stroke and cardiometabolic complications. This simple anthropometric screening approach and health education are expected to increase public awareness and reduce the incidence of stroke, especially in productive age. Keywords: Stroke, Education, Screening, Anthropometry